2018
DOI: 10.1103/physrevlett.121.204501
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Droplet Clustering in Atmospheric Clouds: 3D Radial Distribution Function from Airborne Digital Holography

Abstract: The extent of droplet clustering in turbulent clouds has remained largely unquantified, and yet is of possible relevance to precipitation formation and radiative transfer. To that end, data gathered by an airborne holographic instrument are used to explore the three-dimensional spatial statistics of cloud droplet positions in homogeneous stratiform boundary-layer clouds. The three-dimensional radial distribution functions g(r) reveal unambiguous evidence of droplet clustering. Three key theoretical predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…Turbulent flows laden with inertial particles constitute an active research area within multiphase fluid mechanics due to their potential applications in fields such as planetary formation, pollutant modeling, and cloud formation [3,4]. Several methods are available to characterize particle-clusters, with Voronoï-tessellation [5,6,7,8] becoming increasingly popular in both experimental studies employing visualization techniques, e.g., Particle Tracking Velocimetry (PTV) [2,9] and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulent flows laden with inertial particles constitute an active research area within multiphase fluid mechanics due to their potential applications in fields such as planetary formation, pollutant modeling, and cloud formation [3,4]. Several methods are available to characterize particle-clusters, with Voronoï-tessellation [5,6,7,8] becoming increasingly popular in both experimental studies employing visualization techniques, e.g., Particle Tracking Velocimetry (PTV) [2,9] and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless the magnitude of the instantaneous pair-correlation function at short distances from the collector drop must be nearly what it sees over that distance of fall. Larsen et al (2018) found that at a distance of 1 mm the magnitude of the pair correlation function is ∼10 −2 , for clouds with dissipation rates ∼10 −4 − 10 −3 m 2 ⋅s −3 . For shorter distances still we must rely on estimates from numerical studies based on simple model flows characterized by relatively low Reynolds number.…”
Section: Resultsmentioning
confidence: 97%
“…For the 40 µm collector drop U ≈ 0.3 m·s −1 (Rogers and Yau, ) and for cumulus clouds ε ≤ 10 −1 m 2 ·s −3 (Grabowski and Wang, ), hence L could be of the order of a metre as per our crude scaling argument. However, this is likely an overestimate, since the most intense clustering is found to be at the dissipation scales, as revealed also by the recent in‐cloud measurements (Larsen et al ., ). Hence L cannot be far from the dissipation scale of the in‐cloud turbulence.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations